Durability of Pinus elliottii wood impregnated with quebracho colorado (Schinopsis balansae) bio-protectives - C. Bernardis, Aldo; Popoff, Orlando (Maderas. Ciencia y Tecnología, 2025)
Some wood preservatives have a warning due to environmental restrictions and risks to man health. The aim of this study is to determine the performance of non impregnated and impregnated wood with a CCA salt and a bio-protective made from “quebracho colorado”, when facing the action of fungi responsible for white rot decay by Pycnoporus sanguineus and brown rot attack by Gloeophyllum se-piarium. Wood samples were impregnated with different solutions by vacuum-pressure method. The design was in complete blocks at random with ﬁ ve repetitions. The treatments were T0: non impreg-nated blank sample; impregnated T1: CCA; T2 Colatan IPG-F, T3: Colatan IPG-C, T4: Colatan IPG-C, with retentions of: 6, 18, 9 and 25 kg m-3 respectively. The variable was wood weight loss. Preservative CCA and bio-protective Colatan IPG-C increased the resistance to fungal degradation in lab assay, changing from non-resistance to very resistant (Findlay criterion), guaranteeing the biodegradation process inhibition.